Rv2617c and P36 are virulence factors of pathogenic mycobacteria involved in resistance to oxidative stress - Forrellad, Marina Andrea; Vazquez, Cristina Lourdes; Blanco, Federico Carlos; Klepp, Laura Ines; Garcia, Elizabeth Andrea; Rocha, Rosana Valeria; Villafañe, Luciana Maria; Bigi, María Mercedes; Gutierrez, Maximiliano Gabriel; Bigi, Fabiana (Taylor & Francis, 2020)
In this study, we characterized the role of Rv2617c in the virulence of Mycobacterium tuberculosis. Rv2617c is a protein of unknown function unique to M. tuberculosis complex (MTC) and Mycobacterium leprae. In vitro, this protein interacts with the virulence factor P36 (also named Erp) and KdpF, a protein linked to nitrosative stress. Here, we showed that knockout of the Rv2617c gene in M. tuberculosis CDC1551 reduced the replication of the pathogen in a mouse model of infection and favored the trafficking of mycobacteria to phagolysosomes. We also demonstrated that Rv2617c and P36 are required for resistance to in vitro hydrogen peroxide treatment in M. tuberculosis and Mycobacterium bovis, respectively. These findings indicate Rv2617c and P36 act in concert to prevent bacterial damage upon oxidative stress.